Brainstem Infarction and Vertebral Artery Vasculopathy After Ramsay Hunt Syndrome. (24th May 2022) - Sun, Huiying; You, Hui; Wu, Haiyan
Abstract : A 45-year-old man presented with right auricle rash, facial weakness, otalgia, deafness, and transient dizzy spells. He had leftward spontaneous, bidirectional gaze-evoked and unsuppressed leftward head-shaking nystagmus in head-shaking tilt suppression test (Figure 1). MRI results showed a subacute infarct on the right dorsolateral pons and medulla oblongata and incomplete flow void in the right vertebral artery. After acyclovir and dexamethasone therapy, the ischemic lesion and vascular narrowing on MRI vanished and the patient's symptoms disappeared (Figure 2). Concomitant intracranial vasculopathy and brainstem stroke may occur in Ramsay Hunt syndrome, 1, 2 which could be easily missed but possibly detected by careful eye movement assessments.